Spatial Analysis of the Distribution of Heavy Metals Pb and Cb in Well Water Around Terjun Landfill in Medan City - Raihan Uliya; T. Alief Aththorick; Bejo Slamet; T Sabrina; Rahmawaty (TALENTA Publisher, Universitas Sumatera Utara, 2025)
The study analyzed the spatial distribution of lead (Pb) and cadmium (Cd) in well water around the Terjun Landfill in Medan City. The research aimed to determine Pb and Cd concentrations in dug and drilled wells, compare their levels, and assess the impact of proximity to the landfill's active zone. A total of 22 wells located 50–500 meters from the landfill were sampled using purposive sampling. Spatial analysis was conducted using GPS, while differences in Pb and Cd levels between well types were analyzed using a t-test (α = 0.05, CI 95%). Results showed that Pb concentrations in dug wells ranged from 0.0039 to 0.0379 mg/L, with the highest levels found near SG1 and SG4, indicating landfill influence. In contrast, Pb levels in drilled wells were lower (<0.0001 to 0.0158 mg/L) and primarily influenced by external sources. Cd concentrations ranged from 0.0008 to 0.0032 mg/L in dug wells and 0.0005 to 0.0102 mg/L in drilled wells, with contamination in drilled wells linked to external activities. Proximity to the landfill significantly affected Pb levels in dug wells but had no impact on drilled wells, while Cd levels were unaffected by distance in both well types. The findings suggest that transitioning from dug wells to drilled wells is essential to reduce heavy metal exposure and ensure safer water quality for residents.